Dreams and religious conversions : A study of Malaysian Muslim converts - Suhaila, Abdullah; Mohd Nizam, Sahad; Siti Aishah, Chu Abdullah (Universitats - Bibliothek Heidelberg, 2019)
This study attempts to implement the Islamic mode of dream interpretation as well as assess its significance in religious conversion by examining the Muslim converts’ form of dreams, whereby their dreams were studied in terms of religious dream imageries and dream elements, and eventually, the impacts of religious dream imageries and dream elements to them. It is discovered that the religious dream imageries of the seven participants were explicit and implicit with specific forms of messages such as paradise and hell revealed through dream, reminder dreams, contemplate-like dreams, and ‘savior’ dreams. Results also reveal that the 10 most frequent dream elements recounted by the seven participants were garment (robe), servant of God, turban, elderly person, imam (religious leader), lights, mosque, prayer mat, Qur’an, and sky. The results expose that the impacts of the religious dream imageries and dream elements to the participants were that they either seek for an answer, followed the instructions or hints given in the dreams, or straight away made the decisions to embrace Islam - all of which eventually led them to their conversions to Islam. Thus, dream imageries and dream elements are two aspects that rely on one another in the course of interpreting dreams. The participants’ dreams show that dreams facilitated the reception of religious beliefs by providing personal experiential confirmation of incoming information or events to dreamers.